Evaluation of Good Governance Implementation in Digital Transformation of Public Services - Frangky Erwin Dede Robial; Lady Grace Jane Giroth; Verselia Salindeho (Universitas Muhammadiyah Gorontalo, 2025)
Digital transformation in public services is an important part of efforts to improve good governance. This study aims to measure the effectiveness of the implementation of good governance principles in Mandolang, identify obstacles and supporting factors in digital service management, and design strategies to strengthen digital governance in accordance with the local context. This research evaluates the implementation of good governance principles in the digital transformation of public services in Mandolang District, North Sulawesi. Using a qualitative method with a case study approach, data were collected through interviews, observations, and analysis of policy documents. The results indicate significant challenges related to infrastructure, human resource capacity, and digital literacy among the public. The research also identified supporting and hindering factors and developed a digital governance strengthening strategy relevant to the local context. This study contributes an implementation evaluation model for digital public services at the sub-district level, serving as a basis for policy development and improving the quality of government bureaucracy towards greater transparency and participation.